Getting beneath the surface in program planning, monitoring and evaluation: Learning from use of participatory action research and theory of change in the CGIAR Research Program on Aquatic Agricultural Systems. Issue 1 (March 2017) - Apgar, J Marina; Allen, Will; Albert, Joelle; Douthwaite, Boru; Paz Ybarnegaray, Rodrigo; Lunda, Jeston
Many rural poor and marginalized people strive to make a living in social-ecological systems that are characterized by multiple and often inequitable interactions across agents, scale and space. Uncertainty and inequality in such systems require research and development interventions to be adaptive, support learning and to engage with underlying drivers of poverty. Such complexity-aware approaches to planning, monitoring and evaluating development interventions are gaining strength, yet, there is still little empirical evidence of what it takes to implement them in practice. In this paper, we share learning from an agricultural research program that used participatory action research and theory of change to foster learning and support transformative change in aquatic agricultural systems. We reflect on our use of critical reflection within participatory agricultural research interventions, and our use of theory of change to collectively surface and revisit assumptions about how change happens. We share learning on the importance of being strengths-based in engaging stakeholders across scales and building a common goal as a starting point, and then staging a more critical practice as capacity is built and opportunities for digging deeper emerge.